2020
DOI: 10.14293/s2199-1006.1.sor-.ppktxzi.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Case Item Creation and Video Case Presentation as Summative Assessment Tools for Distance Learning in the Pandemic Era

Abstract: There is an urgent need for more diverse methods for student evaluation, given the sudden shift to online learning necessitated by the Coronavirus Disease 2019 (COVID-19) pandemic. Innovative assessment tools will need to cover the required competencies and should be used to drive self-learning. Self and peer assessments may be added to the traditional classroom-based evaluations in order to identify individual insecurities or overconfidence. Identification of these factors is essential to medical education and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
6
0
2
Order By: Relevance
“…The other experts agreed with the expert's suggestion to include this as a second subcomponent to the first component. Such a claim is consistent with those made by Amin et al (2021) and Chowdhury (2019), who caution that inadequate explanations for learning assessments will result in lacklustre performance from students. Students would readily understand the evaluation requirements if they were given a pertinent assessment rubric, which would help them produce high-quality assignments.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The other experts agreed with the expert's suggestion to include this as a second subcomponent to the first component. Such a claim is consistent with those made by Amin et al (2021) and Chowdhury (2019), who caution that inadequate explanations for learning assessments will result in lacklustre performance from students. Students would readily understand the evaluation requirements if they were given a pertinent assessment rubric, which would help them produce high-quality assignments.…”
Section: Discussionsupporting
confidence: 84%
“…Different technologies have been employed in student learning evaluation over the past few years, and right now video-based assessments are becoming more and more common (Amin et al, 2021;Lewis et al, 2020;Malisius, 2018;Mat Tahir et al, 2019;Rivera & Heinrich, 2016). This is not surprising given that numerous studies have demonstrated how using video-based assessment tools can help students better understand the ideas they are learning by allowing them to analyse real-world issues and develop and assess novel solutions (Gama & Barroso, 2013;Morgan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this situation is that standardized examinations are made with multiple-choice questions, they take less time, and the education process needs assessment-evaluation through multiple-choice question models. Studies conducted by (Hebebci et al, 2020;Sahbaz, 2020;Ilmiyah & Setiawan, 2020;Amin et al, 2020) show that methods that do not take much time in assessment and evaluation in online education and that can meet the needs of students standardized examinations are preferred. It is seen that on EBA TV lessons, filling in the blanks (gap filling) and, open-ended questions are partially used, the matching method is never used, and the true-false method is applied rarely.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini berdampak pada sistem pembelajaran di kampus tidak efektif karena tidak adanya pertemuan tatap muka fisik. Pergeseran mendadak dari pendidikan dan penilaian tatap muka menjadi sepenuhnya online membawa banyak tantangan bagi fakultas, mahasiswa, dan administrasi (Amin et al, 2020). Hal ini membuat para staf pengajar harus kreatif dalam menyiapkan konten pembelajaran (Wijayanto, 2020).…”
Section: Pendahuluanunclassified
“…Penugasan proyek telah digunakan selama beberapa tahun dan dirancang untuk mengembangkan pemahaman mahasiswa dan mendorong ke arah belajar mandiri (Amin et al, 2020). Proyek video memberikan beberapa manfaat bagi mahasiswa dengan menciptakan ruang kelas yang lebih dinamis dan interaktif bersama serta mengembangkan sikap saling ketergantungan positif dan akuntabilitas individu (Aksel & Gürman-Kahraman, 2014).…”
Section: Pendahuluanunclassified